Inventive Activity of Researchers: Cross-Country Rating Assessments - Volkova, Tatyana Ivanovna; Usoltsev, Ivan Aleksandrovich (Economy of Regions, 2017)
In recent years, the study of the research capacity of the country and regions has become more active not only from the point of view of their leading components (personnel, financial, information, organizational, material-and-technical ones) but also from the perspective of the assessment of productivity and effectiveness of researchers' work. In the cross-country analysis, the certain highly aggregative parameters, which values, as a rule, are not in favour of Russia, are used. At the same time, at profound studying of this topic, these estimates cannot represent correctly the real trends of inventive activity in the scientific and technological sphere of the country and its regions. Moreover, the measurement of the researchers' creative potential realization is carried out mainly through the assessment systems of their printing activity. Little attention is paid to the problem of the rating assessments of the researchers' inventive and patent activity and its products from a cross-country perspective (especially to the detailed ones) as well as to its institutional determinants. Therefore, the authors have chosen this subject-matter of the research. Its empirical basis is the statistical materials of both the national database and those which are recognized by the world scientific community. This research has both theoretical and methodological orientations. The purpose is the development of methodological and methodical tools of the research and assessment of researchers' inventive activity including methodological support of cross-country comparative assessments. The authors have based the hypothesis on their previous research: in the conditions of the decreasing level of financial security, continuous reduction of a number of researchers, institutional restrictions and contradictions, the inventive activity of national researchers is still exist, and in a number of its leading parameters is implemented at the level of the advanced countries of the world. From the point of view of the purpose and objectives of the research, we have used the parametrical model with the allocation and assessment of such parameters, methods and indicators, which provide the integrated assessment of the dynamics of inventive and patent productivity and effectiveness allowing to reach the high level of reliability. The authors have applied the following methods: dialectic and gnoseological one, structural and logical one, structurally functional one, the method of decomposition, the method of statistical groups and index method. A transition from the traditional analysis with parameters and indicators of the high aggregated level to the level of their expedient specification has been carried out. The authors have introduced the specified new key indicators grouped by the criteria: inventive activity; patent activity and effectiveness. The article proves the rationale for a dialectic combination of the process oriented estimates, efficiency evaluations and vector (reflecting development trends) estimates. The results of this research can be considered in the case of the development of management decisions by the relevant structures, which are responsible for scientific and technological, and innovation policy at all levels of the power and management.